Determinación etiológica de la otitis en pacientes caninos utilizando como métodos diagnósticos la videotoscopía, citología y cultivo en el hospital veterinario All Pets de la ciudad de Quito - Mendoza Cadena, Tito Jorge (2011)
Among the skin diseases that affect dogs and cats is the ear, which is a condition of acute or chronic inflammatory type, which can be located on the pinna, the ear canal (outer and middle) and the eardrum. Over time there have been several studies of this disease, which have been mainly focused on the identification of factors that produce it, especially when you have seen the fatal consequences (aural hematoma, ruptured eardrum, and even amputation of the affected ear ) to which the ear leads. In studies have shown that this condition is caused by several factors which can be classified as predisposing, primary or secondary and perpetuating; hence its complexity both from the standpoint of diagnostic and therapeutic.